Implementation of Teaching Practices in Improving the Teaching Quality of Final Grade Students of Tarbiyatul Mu'allimaat Al-Islamiyah (TMI) Al-Amien Prenduan Sumenep-Madura 2022 - Musleh Wahid; Roaini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Tarbiatul Mu'allimaat Al-Islamiyah (TMI) Al-Amien Prenduan as an institution that implements teaching practices for final grade female students. Various support is provided in this teaching practice to improve the quality of female students' teaching. This is done to foster an educational spirit in female students before going directly into the wider community in accordance with the Vision and Mission of the Al-Amien Prenduan Islamic boarding school, namely preparing superior and qualified individuals to create the best community ever created for humanity (kahairo ummah). Even though they do not aspire to be teachers, they have been equipped to become quality and professional teachers. Whatever their profession, they will become teachers in the future. This makes the author interested in researching this activity. Researchers conducted this research with the aim of finding out the application of teaching practices and evaluating the teaching practices of Tarbiyatul Mu'allimaat Al-Islamiyah (TMI) Putri Al-Amien Prenduan. This research is descriptive qualitative research. Data collection techniques use interview methods, observation and documentation. Meanwhile, data analysis uses data collection, reduction and presentation. Data validity techniques by means of diligent observation, triangulation and data checking. The results of this research findings were obtained from interviews and documentation which can be concluded in several points. First, a neat system of planning, implementation and evaluation. Second, this teaching practice is so that children can adapt various teaching methods to suit the material. Third, TMI Putri Al-Amien Prenduan has equipped its female students to become educators. The evaluation can be seen from the quality alumni, the supporting factors can be seen from the curriculum, and the inhibiting factors come from the people themselves.